EVALUATION OF ABUTMENT TEETH IN FIXED PARTIAL DENTURE- A RETROSPECTIVE ANALYSIS OF THE PATIENT RECORDS - Kannan, Roghith; Hima Sandeep, Adimulapu; Duraisamy, Revathi (International Journal of Psychosocial Rehabilitation, 2020)
One of the most frequent iatrogenic mishaps during root canal treatment of posterior teeth is perforation of the pulpal floor during access opening/biomechanical preparation. It leads to an open communication between the root canal system and the supporting tissues of the tooth leading to formation of serous exudates, sinus at the site of perforation if left untreated. The development of different techniques and newer materials has led to success in perforation repairs. The main objective of this study was to evaluate perforation repair in furcal involving maxillary molars in patients under 50 years of age. The current study is an institutional based retrospective study performed over reviewing 86,000 case records. A total of 14 subjects who underwent furcal perforation repair in relation to maxillary molars under 50 years of age were chosen for the study out of 6475 subjects who had undergone root canal treatment in various teeth. Patients with other than perforation repairs and medically compromised were excluded. Once the data was obtained, analysis was done by descriptive and inferential statistics using SPSS by IBM version 20. From this current study, it was found that, out of 14 patients, 9 males (64.29%) and 5 females (35.71%) have undergone perforation repair treatment. Highest incidence of perforation repair was seen in tooth number 26 (42.86%). Patients in the age group of 41-50 years had the highest incidence of perforation repair in relation to maxillary molars. Adequate knowledge, experience and clinical skill enables good management of furcal perforations.